Castilla y León, Between the Earth and the Screen: New Narrative Perspectives (Castilla. Estudios de Literatura, 2017)
The influence of the Information and Communication Technologies’ (ICT) causes socio-cultural important changes that propitiate the transgression of traditional models in art. Good examples about it are in western narrative that is approaching to the experimental literature through the incorporation of formal or thematic resources from the mass media and its culture. Some young writers from Castile and Leon, as Ángel Vallecillo, Miguel Espigado or Javier García Rodríguez, have been incorporated into this tendency.
Keywords: narrative; Castile and Leon; TIC; ICT; globalization; experimental literature